2014
DOI: 10.1007/s00535-014-1028-x
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel injury in low-dose aspirin users

Abstract: The use of low-dose aspirin (LDA) is well known to be associated with an increased risk of serious upper gastrointestinal complications, such as peptic ulceration and bleeding. Until recently, attention was mainly focused on aspirin-induced damage of the stomach and duodenum. However, recently, there has been growing interest among gastroenterologists on the adverse effects of aspirin on the small bowel, especially as new endoscopic techniques, such as capsule endoscopy (CE) and balloon-assisted endoscopy, hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 75 publications
0
19
0
5
Order By: Relevance
“…The role of APAs in causing colonic bleeding, mainly in diverticula, has been pointed out more recently [33]. Similarly, small bowel bleeding caused by APAs, mainly erosive enteropathy, is increasingly recognized [32]. …”
Section: Antiplatelet Therapymentioning
confidence: 99%
“…The role of APAs in causing colonic bleeding, mainly in diverticula, has been pointed out more recently [33]. Similarly, small bowel bleeding caused by APAs, mainly erosive enteropathy, is increasingly recognized [32]. …”
Section: Antiplatelet Therapymentioning
confidence: 99%
“…Various features of gastrointestinal lesions due to LDA have been described such as multiple petechiae, loss of villi, erosions, and round, irregular, and punched-out ulcers [ 10 ]. In fact, it is difficult to diagnose the cause of small bowel injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have shown that aspirin is associated with an inammatory state via the expression of proinammatory cytokines. 4,36 Although, inammatory state and oxidative stress are intimately linked, as shown by the constant elevation of oxidative stress markers during inammatory bowel disease. 54 Thus, taking antioxidants is an important therapeutic strategy for ghting inammation.…”
Section: Discussionmentioning
confidence: 99%